Design of an Educational Game for Children: 'Geometry Forest' Using Construct 2 - Retno, Sujacka (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2025)
Early childhood education plays a crucial role in building the foundational knowledge and skills that will be used throughout life. This study aims to design and develop an educational game titled